Experimental test of the heating and cooling rate effect on blocking temperatures - Berndt,T; Paterson,GA; Cao,C; Muxworthy,AR (Geophysical Journal International, 2017)
The cooling rates at which rocks acquire thermoremanent magnetizations (TRMs), affect their unblocking temperatures in thermal demagnetization experiments; similarly the heating rates at which the thermal demagnetization experiments are done also affect the unblocking temperature. We have tested the effects of variable cooling and heating rates on the unblocking temperatures of two natural non-interacting, magnetically uniform (single-domain, SD) (titano)magnetite samples and a synthetic SD magnetoferritin sample. While previous studies have only considered unblocking temperatures for stepwise thermal demagnetization data (i.e. the room-temperature magnetization after incremental heating), in this work we derive an expression for continuous thermal demagnetization of both TRMs and viscous remanent magnetizations (VRMs) and relate the heating rate to an effective equivalent hold time of a stepwise thermal demagnetization experiment. Through our analysis we reach four main conclusions: First, the theoretical expressions for the heating/cooling rate effect do not accurately predict experimentally observed blocking temperatures. Empirically, the relation can be modified incorporating a factor that amplifies both the temperature and the heating rate dependence of the heating/cooling rate effect. Using these correction factors, Pullaiah nomograms can accurately predict blocking temperatures of both TRMs and VRMs for continuous heating/cooling. Second, demagnetization temperatures are approximately predicted by published ‘Pullaiah nomograms’, but blocking occurs gradually over temperature intervals of 5–40 K. Third, the theoretically predicted temperatures correspond to ∼54–82 per cent blocking, depending on the sample. Fourth, the blocking temperatures can be used to obtain estimates of the atomic attempt time τ0, which were found to be 3 × 10−10 s for large grained (titano)magnetite, 1 × 10−13&t